The development of the right to privacy in the light of freedom of expression - Sigurður Pétur Hjaltason (2006)
Verkefnið er lokað In this thesis, the tension between the freedom of expression and the right to privacy is examined with particular attention to the media in Iceland and the United Kingdom. I will consider how these rights are protected in international treaties, especially protection under the European Convention of Human Rights, constitutional protection, domestic laws and cases. The Von Hannover v Germany case is summarized, as is its impact on the right to privacy in Europe. Following the Von Hannover case, the line between freedom of expression and right to became a little clearer and for the first time in a long period a guideline was set for adjudicating the conflicts between privacy and the media. The main question in the thesis is whether there has been a change in the relations between freedom of expression and the right to privacy or if the "landmark judgment" in the Von Hannover case was unique and restricted to its own facts with no precedent effects and therefore unlikely to change anything. In the light of the Von Hannover ruling, cases in Iceland and the UK will be evaluated and the development examined. In addition, the importance of ethical codes in the media profession has been disputed and I will try to evaluate the significance of these codes and their role in the media profession.